Advanced flexible ceramics : design, properties, manufacturing, and emerging applications - Gupta, Ram; Behera, Ajit; Farhad, Siamak; Nguyen, Tuan Anh (Chemist) (Elsevier series on advanced ceramic materials., 2023)
Advanced Flexible Ceramics: Design, Properties, Manufacturing, and Emerging Applications provides detailed information on the properties and applications of advanced flexible ceramics. Sections cover materials dependent flexible behavior, microstructure and phases, the operational life of ceramics, how flexible materials can influence smart behavior (shape memory and self-healing), and thermal, physical, mechanical, electrical and optical properties. Various processing routes such as powder metallurgy, both physical and chemical vapor deposition, sol-gel, 3D print, and roll-to-roll processing are also explained in detail. The later section of the book provides detailed coverage of emerging technological applications. Additional chapters cover cost-effectiveness and the global market and recycling and future challenges and perspectives. This will be an essential reference resource for academic and industrial researchers working in the fields of refractory linings, high-temperature equipment, shielding, and MEMS/NEMS.